Preliminary Analysis of Regeneration Possibilities of The Tourism Industry After the Coronavirus Pandemic - Magdalena SZOPA; Piotr HALEMBA (Communications of International Proceedings, 2020)
The pandemic of the infectious disease COVID–19 caused by the SARS–Cov–2 coronavirus, officially announced by the WHO on March 11, 2020, has hit the global economy on multiple fronts. This paper analyzes the impact of the pandemic on the tourism sector and its ability to regenerate once the pandemic has ended. The subject of the research was the occupancy rate of bedrooms and bed-places in hotels and accommodation of a similar type according to the NACE 55.1 classification in five selected countries of the European Union in the period from January to July 2020 with the background of the occupancy rates in the years 2012–2019. The results have shown that even though the tourism sector has experienced a drastic decline in the face of the coronavirus pandemic, the occupancy rates in the analyzed countries quickly began to increase as soon as it was possible. With this observation the hypothesis about the high regeneration capacity of the tourism industry has been proven. This preliminary analysis allows for an optimistic view of the future of tourist services both for the ending of the pandemic and the sector surviving other possible crises in the future.
Keywords: COVID-19 Pandemic; Tourism; Industry; Regeneration